New record of Brachycephalus fuscolineatus Pie, Bornschein, Firkowski, Belmonte-Lopes & Ribeiro, 2015 (Anura, Brachycephalidae) from Santa Catarina state, Brazil - Bornschein, Marcos Ricardo [UNESP] (2019)
Brachycephalus fuscolineatus Pie, Bornschein, Firkowski, Belmonte-Lopes & Ribeiro, 2015 was described from Morro do Baú, Santa Catarina, Brazil. This species occurs at elevations of 640–790 m, and it is known to have an extent of occurrence of 23.63 ha. Here, we report a new record of B. fuscolineatus from Morro Braço da Onça, Luiz Alves, Santa Catarina. We recorded it on 21–22 December 2018 at elevations between 525 and 530 m; the new record occupied an area of 0.19 ha. We estimate 9 calling males in 36.35 m2.